Delayed diagnosis of STAT1 gain-of-function variant in a patient with multiple endocrine autoimmunity and recurrent fungal infections - Sydney Sparanese; Rae Brager; David Fahmy; Jenny Garkaby (Endocrinology, Diabetes & Metabolism Case Reports)
This case report describes a 54-year-old woman with multiple endocrine autoimmune pathologies and recurrent mucocutaneous Candida spp. infections that were inappropriately attributed to her glycemic control. Following an allergic reaction over four decades later, the patient was referred to clinical immunology. The combination of persistent Candida infections, autoimmune endocrinopathies, and a positive family history prompted investigation for an inborn error of immunity (IEI). Genetic testing revealed a novel, missense mutation in STAT1. Functional analysis confirmed enhanced STAT1 protein phosphorylation, confirming a gain-of-function phenotype that explained her infectious and autoimmune manifestations. She was started on the JAK inhibitor, ruxolitinib, with clinical improvement. This case underscores the shared molecular mechanisms between IEIs and autoimmune endocrinopathies and highlights the importance of early recognition of IEI in patients with unusual or treatment-refractory infections alongside autoimmune disease. Endocrinologists and primary care providers may be the first to encounter such patients and should consider referral for immunologic and genetic evaluation. Early diagnosis can reduce long-term morbidity and open the door to targeted therapies that address the root cause of immune dysregulation.